Reformulation of the Government Compilation of Islamic Law: Strengthening the Concept of Gender-Sensitive Regulations in Indonesia - Fauna Alwy (Universitas Lampung, 2017)
The main purpose of this study is to find out the weaknesses in the application of the Compilation of Islamic Law in Indonesia, especially some of the provisions in it that tends to be gender biased; so that innovative ideas can be found to strengthen even the re-formulation of gender-sensitive legislation but still based on Shariah values and customary law. It is normative law research that uses a normative legal case study in the form of legal behavior products, among others by examining the Compilation of Islamic Law especially in the level of its implementation. The subject of the study is the Islamic marriage law which is conceptualized as the norm or rule that applies in the society and becomes the reference of behavior for every Indonesian citizen who embraced Islam.Keywords: Reformulation, Government Compilation, Islamic Law, Strengthening, Concept, Gender Sensitive Regulations